Comparative Analysis of Qualitative and Quantitative Phytochemical Evaluation of Selected Leaves of Medicinal Plants in Jaffna, Sri Lanka - Gowri Rajkumar; Panambara Arachchilage Harini Rangana Panambara; Vinotha Sanmugarajah (Borneo Journal of Pharmacy, 2022)
The traditional system of medicine in Sri Lanka has shown much better improvement, has fewer side effects, and is less expensive than modern synthetic drugs in the treatment of many diseases. The objective of the present study was to comparatively evaluate the qualitative and quantitative analysis of phytochemical constituents of leaves of Murraya koenigii (L.) Spreng., Tinospora cordifolia (Wild) Hook.f., Enicostemma axillare (Lam) A. Raynal, and Gymnema sylvestre R. Br. were collected from Jaffna District. The shade-dried leaves were powdered and extracted with ethanol using the cold extraction technique. These ethanolic extracts were subjected to phytochemical analysis using recommended laboratory techniques. The one-way analysis of variance (ANOVA) and Tukey's multiple comparisons at probability value (p <0.05) were used in the statistical analysis of the data. Phytochemical screening showed the presence of alkaloids, flavonoids, tannins, terpenoids, steroids, saponins, phenols, and glycosides. Murraya koenigii shows the highest phenol and alkaloid contents (1960.71±66.88 and 19.42±0.26). Enicostemma axillare shows the highest flavonoid and tannin contents (22.27±0.86 and 1.26±0.017). Therefore, E. axillare and M. koenigii can be used as nutraceuticals in traditional medicine.